ENHANCEMENT OF TRANSMISSION CAPACITY IN DEREGUALTED POWER SYSTEM-AN OVERVIEW - PROF. DR. N. G. SAVAGAVE; MR. D. D. GAVALI; MR. D. A. PATIL (International Journal of Innovations in Engineering Research and Technology, 2021)
In this paper review of few pioneer for transmission planning in deregulated environment is been studied and most critical observations are marked. Expansion planning of approaches may be different and it depend upon the type of market is been used for making deregulated environment. Two models are very much possible one is fully adopted in UK and other in US. The two models are discussed in a great detail in literature. Broadly speaking there are only two transmission planning approaches are possible deterministic and non deterministic.